2019
DOI: 10.1016/j.ejvs.2018.10.038
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of the Presentation and Surgical Management of Patients With Carotid Body Tumours

Abstract: WHAT THIS PAPER ADDS This is the largest systematic review and meta-analysis detailing the presentation, management, and procedural complications following carotid body tumour (CBT) surgery. Although relatively rare, complications associated with CBT are not inconsiderable, especially in the more challenging Shamblin III CBTs where procedural stroke rates were about 4%, while cranial nerve injury rates approached 20%. The increasing morbidity associated with Shamblin III tumours must be considered during the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
127
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(150 citation statements)
references
References 80 publications
14
127
2
7
Order By: Relevance
“…Our 30‐day results are an improvement on those presented in the most extensive meta‐analysis carried out to date (with 4418 patients and 4743 CPGs) 14 . The percentages of morbidity and mortality are lower in relation to stroke (2.4% vs 3.5%), cranial nerve injury (16.7% vs 25.4%), and mortality (0% vs 2.2%).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Our 30‐day results are an improvement on those presented in the most extensive meta‐analysis carried out to date (with 4418 patients and 4743 CPGs) 14 . The percentages of morbidity and mortality are lower in relation to stroke (2.4% vs 3.5%), cranial nerve injury (16.7% vs 25.4%), and mortality (0% vs 2.2%).…”
Section: Discussionsupporting
confidence: 49%
“…In addition to an American registry, 5 the CPGs published in PubMed do not exceed 5000 cases. 7,14 Therefore, if CPGs are infrequent, the complex forms we discuss below are even more rare (Table 5). Low frequency and high complexity pose a challenge for the surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…The other important point is early division of the feeding vessels to the tumor to reduce the amount of tumor bleeding. Paragangliomas usually receive their blood supply from the branches of external carotid artery, most commonly from the ascending pharyngeal branch [ 11 ]. Some authors have asserted the importance of preoperative tumor embolization to reduce intraoperative bleeding and to allow easier dissection during the removal of the hypervascular tumor [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…HNPGLs associated with cranial nerves are often best followed with active surveillance if asymptomatic and may be treated with external beam radiation with local control achieved in 79-100 % of cases [123]. The largest meta-analysis to date of observational and retrospective studies (no randomized controlled trials exist for these rare tumors) for the surgical resection of > 4000 CBTs showed that Shamblin classification [124] [28]. Overall CVA rate was 3.5 %, cranial nerve injury persisting beyond thirty days after resection was 11.5 %, and preoperative embolization did not reduce postoperative cervical hematoma [28].…”
Section: Head and Neck Paragangliomasmentioning
confidence: 99%
“…The largest meta-analysis to date of observational and retrospective studies (no randomized controlled trials exist for these rare tumors) for the surgical resection of > 4000 CBTs showed that Shamblin classification [124] [28]. Overall CVA rate was 3.5 %, cranial nerve injury persisting beyond thirty days after resection was 11.5 %, and preoperative embolization did not reduce postoperative cervical hematoma [28]. Another study of 20 resected CBTs showed that cranial nerve injury was more likely to occur during resection of high riding CBTs as determined on preoperative imaging (superior tip of C2 dens to superior border of CBT = 1.8 vs. 2.9 cm, p < 0.01) [125].…”
Section: Head and Neck Paragangliomasmentioning
confidence: 99%